TURKISH CONSUMER DECISIONS AFFECTING ICE CREAM CONSUMPTION - Yavuz Topcu (Chiriotti Editori, 2015)
The aim of the study is to determine the main factors affecting the national-branded ice cream preferences of Turkish consumers, and to analyze the relationships between their preferences and consumption amounts. The data obtained from 400 households in Kahramanmaras, Turkey were used for Principal Component, K-Means Cluster and Multiple Regression Analyses. The results of the study highlighted clearly that the consumers of the high (C1), middle (C2) and low-income users (C3) satisfied with the manufacturer brand, the individual private label, and the retailer brands on the ice cream purchase decision and consumption amounts, respectively. The manufacturers, retailers and marketers of the ice cream, therefore, should implement effectively the manufacturer brand, the private label and the retailer brand for C1, C2 and C3, respectively, and then they could also increase the demand trends of the target consumers segments satisfied.